Endoscopic Ultrasonography May Select Subjects Having Asymptomatic Chronic Pancreatic Hyperenzymemia Who Require a Stricter Follow-up. Issue 4 (April 2017) - Antonini, Filippo; Belfiori, Valerio; Pagano, Nico; Buscarini, Elisabetta; De Minicis, Samuele; Lo Cascio, Massimiliano; Marraccini, Barbara; Piergallini, Simona; Rossetti, Pamela; Andrenacci, Elena; Macarri, Giampiero; Pezzilli, Raffaele
Abstract : Objectives: We have previously shown that at least 50% of patients with asymptomatic chronic pancreatic hyperenzymemia (ACPH) may develop morphological pancreatic alterations. Endoscopic ultrasonography (EUS) may detect small lesions, and its sensitivity seems to be higher than other imaging techniques. The aim of this study was to evaluate whether EUS may modify the management of patients having ACPH. Methods: In 2 referral centers for pancreatic disease, a retrospective analysis of prospectively enrolled patients with ACPH was conducted. Results: Seventy-three patients with ACPH were enrolled for the purpose of this study. Endoscopic ultrasonography was performed as the last examination in 45 subjects who resulted negative at previous imaging studies (abdominal ultrasound, computed tomography, magnetic resonance imaging associated with cholangiopancreatography). Using EUS in 7 subjects, abnormalities were found in the following: 3 branch-duct intraductal papillary mucinous neoplasms, 1 duodenal diverticulum, 1 annular pancreas, 1 findings suggestive of chronic pancreatitis, and 1 undefined cyst (<5 mm). Conclusions: Endoscopic ultrasonography is able to detect alteration not found by other imaging technique in 15.5% of patients with ACPH and may be useful to select those patients who require a more strict follow-up.